Lecturer Performance Analysis at Private Universities in Jakarta - Ronnie Resdianto Masman (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study seeks to see and analyze the effect of compensation on lecturer performance, the work environment on lecturer performance, and organizational commitment on lecturer performance. The result is that compensation has a positive and significant influence on lecturer performance, which means that good compensation can make lecturers work more enthusiastically to conduct good and quality teaching and research to get prestigious research grants both on a local and international scale and to publish the results of lecturers' research. From national journals to highly reputable international journals, and are willing to do community service based on assignments at the university or outside the campus where they work. Organizational commitment has a positive and significant influence on lecturer performance, which means that lecturers have a good commitment to be involved in every campus activity in terms of effective teaching methods to improve campus quality, research with fellow lecturers, research grants on a local to an international scale, conducting activities community service for the sake of educating the life of the nation, synergizing between campuses and companies through the Merdeka Belajar Kampus Merdeka (MBKM) program. Lecturers feel lost if they leave the campus where they work because various facilities are available. In this case, the lecturers become loyal and loyal to work on their campuses, so it is proven to improve the performance of lecturers on their respective campuses. The work environment has an insignificant positive effect on lecturer performance. In this case, the work environment is not a problem for lecturers, such as problems with lighting, comfort and cleanliness, because that has become the campus standard.